Bacterial sex in dental plaque - Olsen, Ingar (Co-Action Publishing, 2013)
Genes are transferred between bacteria in dental plaque by transduction, conjugation, and transformation. Membrane vesicles can also provide a mechanism for horizontal gene transfer. DNA transfer is considered bacterial sex, but the transfer is not parallel to processes that we associate with sex in higher organisms. Several examples of bacterial gene transfer in the oral cavity are given in this review. How frequently this occurs in dental plaque is not clear, but evidence suggests that it affects a number of the major genera present. It has been estimated that new sequences in genomes established through horizontal gene transfer can constitute up to 30% of bacterial genomes. Gene transfer can be both inter- and intrageneric, and it can also affect transient organisms. The transferred DNA can be integrated or recombined in the recipient's chromosome or remain as an extrachromosomal inheritable element. This can make dental plaque a reservoir for antimicrobial resistance genes. The ability to transfer DNA is important for bacteria, making them better adapted to the harsh environment of the human mouth, and promoting their survival, virulence, and pathogenicity.